COVID-19 and its threat to refugees in Africa - Emery Manirambona; Laura Wilkins; Don Eliseo Lucero-Prisno III (Tabriz University of Medical Sciences, 2021)
Although it is widely accepted that coronavirus disease 2019 (COVID-19) has adversely affected the Global South's most vulnerable refugee communities, they have received little attention. There have been gaps in testing, which is fundamental to treat and isolate patients and make data-driven decisions to protect the refugee community. Therefore, it is imperative to holistically implement policies to curtail COVID-19 in refugee camps to ensure that refugees are safe and protected from the pandemic. Processes for timely diagnosis and treatment, quick isolation and contact tracing are essential to keep refugees safe. Furthermore, it is crucial to encourage protective behaviours and raise awareness about hygiene and social prevention to dampen disease transmission. Refugees in the Global South have been disproportionately affected by the consequences of the COVID-19 pandemic, facing financial hardship and social injustice throughout. Refugees in Africa have also faced threats to their security, being subjected to torture, disappearance, or even killings in their host countries. The pandemic has exposed gender inequalities, with females being the most affected, and health inequities in the refugee community in Africa. There is a need for international organizations like the African Union, United Nations (UN) agencies, non-governmental organizations (NGOs), and other stakeholders to take serious action regarding the refugee situation in Africa. Food aid for refugees in Africa should be increased as quickly as possible and refugees' security must be guaranteed. Of equal importance, there must be justice for the death or disappearance of refugees. It is imperative to end discrimination against refugees and support the promotion of gender equity.